The osteoblast secretome in Staphylococcus aureus osteomyelitis - Granata, Valentina; Possetti, Valentina; Parente, Raffaella; Bottazzi, Barbara; Inforzato, Antonio; Sobacchi, Cristina (Frontiers in Immunology, 2022)
Osteomyelitis (OM) is an infectious disease of the bone predominantly caused by the opportunistic bacterium Staphylococcus aureus (S. aureus). Typically established upon hematogenous spread of the pathogen to the musculoskeletal system or contamination of the bone after fracture or surgery, osteomyelitis has a complex pathogenesis with a critical involvement of both osteal and immune components. Colonization of the bone by S. aureus is traditionally proposed to induce functional inhibition and/or apoptosis of osteoblasts, alteration of the RANKL/OPG ratio in the bone microenvironment and activation of osteoclasts; all together, these events locally subvert tissue homeostasis causing pathological bone loss. However, this paradigm has been challenged in recent years, in fact osteoblasts are emerging as active players in the induction and orientation of the immune reaction that mounts in the bone during an infection. The interaction with immune cells has been mostly ascribed to osteoblast-derived soluble mediators that add on and synergize with those contributed by professional immune cells. In this respect, several preclinical and clinical observations indicate that osteomyelitis is accompanied by alterations in the local and (sometimes) systemic levels of both pro-inflammatory (e.g., IL-6, IL-1α, TNF-α, IL-1β) and anti-inflammatory (e.g., TGF-β1) cytokines. Here we revisit the role of osteoblasts in bacterial OM, with a focus on their secretome and its crosstalk with cellular and molecular components of the bone microenvironment and immune system.